2017
DOI: 10.1021/acsmacrolett.6b00906
|View full text |Cite
|
Sign up to set email alerts
|

Shear Banding in Telechelic Associative Polymers by Molecular Dynamics

Abstract: Results on the shear flow of telechelic associative polymers using nonequilibrium molecular dynamics (NEMD) are presented. The particle stream velocities can be calculated from the peculiar velocities and the imposed velocity profile using a novel approach. The constitutive relationship stress–shear rate becomes nonmonotonic when the interaction force between hydrophobic sites is increased. This condition induces a steady banding flow, which arises under transient conditions as a local instability originated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A lot of theoretical and computational studies of rheological properties of physical gels consisting of APs have been reported . Tanaka and Edwards proposed a transient network theory to physical gels consisting of APs and explained the shear thinning under the steady shear flow and the Maxwellian behavior controlled by the dissociation of associating groups from micelles in the linear viscoelasticity regime .…”
Section: Introductionmentioning
confidence: 99%
“…A lot of theoretical and computational studies of rheological properties of physical gels consisting of APs have been reported . Tanaka and Edwards proposed a transient network theory to physical gels consisting of APs and explained the shear thinning under the steady shear flow and the Maxwellian behavior controlled by the dissociation of associating groups from micelles in the linear viscoelasticity regime .…”
Section: Introductionmentioning
confidence: 99%
“…In concentrated solutions of telechelic polymers, i.e. linear chains with stickers at both extremities that enable the formation of transient network, experiments [33,36,37] and MD simulations [38] showed that flow instabilities can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Near the overlap concentration, sticker clusters can be bridged by polymer strands and form an interconnected volume spanning networka physical gel [1][2][3]. Such gels are found in both natural and synthetic systems, and display a striking array of rheological behavior, including strain stiffening [4], negative normal stresses [5], shear thickening [6,7], shear thinning [8], and shear banding [9][10][11][12][13][14][15].Despite the ubiquity and versatility of physical gels, a fundamental understanding of the interplay between their microstructure, dynamics, and rheological properties remains a challenging and open problem. For instance, while experiments and simulations of associative networks (including both AP [13][14][15] and colloidal [16] gels) under simple shear have observed spatial inhomogeneities in both shear rate and density, suggesting some form of sheargradient concentration coupling (SCC) [17][18][19][20], the microscopic mechanism for the instability is unclear.…”
mentioning
confidence: 99%
“…Such gels are found in both natural and synthetic systems, and display a striking array of rheological behavior, including strain stiffening [4], negative normal stresses [5], shear thickening [6,7], shear thinning [8], and shear banding [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation